Factors Affecting The Performance of Health Officers in The Care of Covid-19 Patients at Murni Teguh Memorial Hospital - Bangbang Buhari; Sri Lestari Ramadhani Nasution; Ermi Girsang; Chrismis Novalinda Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
Covid-19 is a respiratory infection caused by the SARS-CoV-2 virus. COVID-19 is transmitted through close physical contact and respiratory droplets and can be transmitted airborne during aerosol procedures. In Indonesia as of January 21, 2021, there have been 951,651 cases with the result that 772,790 patients recovered and 27,203 people died.Nurses treat patients directly at close distances and are often directly exposed to the SARS-CoV-2 virus and have a high risk of experiencing COVID-19 disease (Hope et al, 2011). Preliminary reports suggest that the rate of COVID-19 infection among nurses is higher than during the SARS pandemic (Huang et al, 2020). The World Health Organization reports that more than 22,000 medical workers spread across 52 countries and regions have been infected with the corona virus (Covid-19). This research purpose to find out the factors that affect the performance of health workers in treating Covid-19 patients at Murni Teguh Memorial Hospital. This type of research isquantitative research with a cross sectional approach.This research was conducted in November 2021. There arethe influence of individual factors and organizational factors on the performance of health workers in treating Covid-19 patients at Murni Teguh Memorial Hospital.